An investigation into consulting engineering service quality perceptions and expectations - De Villiers, Gregory Ian (Department of Mechanical Engineering, 2016)
This thesis focuses on the 'Quality of Service' provided by Consulting Civil/Structural engineers. The study assesses whether or not there are shortfalls in the quality of engineering services provided by consulting engineers. It identifies service dimensions that are problematic and also identifies 'real' variables which consulting engineers should manage in order to improve their services. A survey research method was used (pilot and main study) to collect information from management in the consulting industry; and from clients of the consulting engineering profession. The pilot study aimed to determine whether engineers were meeting client expectations; and to what extent formal quality control usage and management support of this, contributed to the delivery of quality services. Furthermore the study aimed to determine whether engineers ever assessed client satisfaction to gather information about providing more accurate services to clients; to determine any costs associated with poor services; and to determine any general service improvements suggested by engineers and clients. The main study aimed to measure the relative size of the gap that existed between the expected and perceived services from clients; as well as the gap across the boundary between clients' expected service and engineers' perceptions of clients' expectations. It was found that on the whole clients were dissatisfied with services received from engineers. This provision of 'poor services' was found to have bigger financial implications to engineers than it did to clients! Three areas of service, were identified which engineers should manage to improve their services i.e. the provision of the optimum solution to the client's exact need, doing this in the allotted time, and tailoring this service to within the client's budget. This was regarded as being superior service provision, and would give engineers the required competitive edge to remain profitable in the market. Includes Bibliography: p. 85.